Inhibitory effect of melatonin on hypoxia-induced vasculogenic mimicry via suppressing epithelial-mesenchymal transition (EMT) in breast cancer stem cells (vol 881, 173282, 2020) - Maroufi, Nazila Fathi; Amiri, Maryam; Dizaji, Babak Faraji; Vahedian, Vahid; Akbarzadeh, Maryam; Roshanravan, Neda; Rashidi, Mohammad-Reza (Elsevier, 2025)
[Abstract Not Available]